Invasive head and neck cutaneous squamous cell carcinoma: clinical and histopathological characteristics, frequency of local recurrence and metastasis - Vasconcelos, Luiza [UNESP] (2014)
BACKGROUND: squamous cell carcinoma is the second most common type of skin malignancy and may evolve to regional lymph node and distant metastases. OBJECTIVE: The objective of this study was to evaluate patients with head and neck cutaneous squamous cell carcinoma to identify its clinical and histopathological characteristics, as well as the frequency of local recurrence and metastasis. METHODS: A retrospective cohort of patients with head and neck cutaneous squamous cell carcinoma. Inclusion criteria: histopathological confirmation, follow-up for longer than one year after diagnosis. Exclusion criteria: immunosuppression; lip and oral cavity squamous cell carcinoma; and non-surgical resection of the lesion. We evaluated demographic, clinical and anatomopathologic findings and explored their associations. RESULTS: Sixty-one patients with 79 tumors and followed by 4.8±3.0 years were selected. The average age was 67.1 years, and 63% of tumors had up to two centimeters. Seven tumors (8.9%) recurred and two of them had positive margins. Recurrence was associated with higher Broders' grade (p<0.01). Two patients (3.3%) had regional lymph node metastases. There were no distant metastases. Seventy tumors were considered to be usual tumors (89.7%), and 68 (87.2%) were classified as Broders' grade 1 and 2. Additionally, 64.1% of tumors had a depth of invasion below four millimeters. Thirteen tumors (16.7%) had positive histological margins. CONCLUSIONS: Most patients had good prognosis in the first year of follow-up, confirming that head and neck cutaneous squamous cell carcinoma has a better prognosis than squamous cell carcinoma of other regions such as mucosa, oral cavity, and internal organs.